Smart Mesoporous Nanomaterials for Antitumor Therapy - Martínez-Carmona, Marina (Nanomaterials (Basel), 2015)
The use of nanomaterials for the treatment of solid tumours is receiving increasing attention by the scientific community. Among them, mesoporous silica nanoparticles (MSNs) exhibit unique features that make them suitable nanocarriers to host, transport and protect drug molecules until the target is reached. It is possible to incorporate different targeting ligands to the outermost surface of MSNs to selectively drive the drugs to the tumour tissues. To prevent the premature release of the cargo entrapped in the mesopores, it is feasible to cap the pore entrances using stimuli-responsive nanogates. Therefore, upon exposure to internal (pH, enzymes, glutathione, etc.) or external (temperature, light, magnetic field, etc.) stimuli, the pore opening takes place and the release of the entrapped cargo occurs. These smart MSNs are capable of selectively reaching and accumulating at the target tissue and releasing the entrapped drug in a specific and controlled fashion, constituting a promising alternative to conventional chemotherapy, which is typically associated with undesired side effects. In this review, we overview the recent advances reported by the scientific community in developing MSNs for antitumor therapy. We highlight the possibility to design multifunctional nanosystems using different therapeutic approaches aimed at increasing the efficacy of the antitumor treatment.